A Non‐Destructive Electrical Assay of Stem Cell Differentiation Based on Semiconductor Biosensing. Issue 2 (1st February 2023) - Hideshima, Sho; Hayashi, Hiroki; Saito, Sayoko; Tateno, Hiroaki; Momma, Toshiyuki; Osaka, Tetsuya
Abstract: Invited for this month′s cover is the collaborating groups of Prof. Sho Hideshima at Tokyo City University, Prof. Tetsuya Osaka at Waseda University, and Prof. Hiroaki Tateno at National Institute of Advanced Industrial Science and Technology, Japan. The cover picture shows a semiconductor‐based biosensor with potential to detect the presence of a specific biomarker of human induced pluripotent stem cell (hiPSCs) in a culture medium. More information can be found in the Research Article by S. Hideshima, T. Osaka, and co‐workers . Abstract : To improve the safety of human‐induced pluripotent stem cells (hiPSCs)‐derived cell therapy products, this work builds on the concept of FET biosensors for detecting actual hiPSCs. This study demonstrated that field‐effect transistor (FET) biosensors have the potential to rapidly inspect the differentiation status of hiPSCs in a non‐destructive manner by detecting the presence of a hiPSC‐specific biomarker in a culture medium. Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/anse.202200046 ).